Choosing and using citation and bibliographic database software (BDS) - Hernandez DA; El-Masri MM; Hernandez CA (Diabetes Educator)
The diabetes educator/researcher is faced with a proliferation of diabetes articles in various journals, both online and in print. Keeping track of cited references and remembering how to cite the references in text and the bibliography can be a daunting task for the new researcher and a tedious task for the experienced researcher. The challenge is to find and use a technology, such as bibliographic database software (BDS), which can help to manage this information overload. This article focuses on the use of BDS for the diabetes educator who is undertaking research. BDS can help researchers access and organize literature and make literature searches more efficient and less time consuming. Moreover, the use of such programs tends to reduce errors associated with the complexity of bibliographic citations and can increase the productivity of scholarly publications. The purpose of this article is to provide an overview of BDS currently available, describe how it can be used to aid researchers in their work, and highlight the features of different programs. It is important for diabetes educators and researchers to explore the many benefits of such BDS programs and consider their use to enhance the accuracy and efficiency of accessing and citing references of their research work and publications. Armed with this knowledge, researchers will be able to make informed decisions about selecting BDS which will meet their usage requirements.